Molecular biology approaches to quantify subcellular localisation of mRNA therapeutics - Smart, Alfredo D. (2025)
Messenger RNA (mRNA) therapeutics hold promise for treating diverse diseases but face delivery challenges, as effective cytosolic entry and subsequent translation are limited by endosomal entrapment. Nanoparticles aid mRNA transport across cell membranes, yet only a fraction of mRNA escapes endosomes to reach the cytoplasm, limiting translational efficacy. Current methods to quantify delivered mRNA localisation lack precision, necessitating more quantitative approaches. This thesis addresses this gap by optimising the APEX2-RT-qPCR proximity biotinylation method to enable quantification of mRNA localisation in both the cytosol and endoplasmic reticulum (ER). Through this approach, the study lays groundwork for examining ER-associated localisation and translation, with preliminary investigation into the impact of signal peptides in directing delivered mRNA to the ER.